Vacation under the volcano - Osborne, Mary Pope. (New York : Random House, 1998)
Their magic tree house takes Annie and Jack to Pompeii just as Vesuvius is about to erupt, and they must find a Roman scroll before everything is covered with burning ash.
"A Stepping Stone book."
L.A. Recommended Foreign Language
2.2
3-6
Keywords: Time travel -- Fiction; Vesuvius (Italy) -- Eruption, 79 -- Fiction; Pompeii (Extinct city) -- Fiction; Tree houses -- Fiction; Time travel -- Fiction; Vesuvius (Italy) -- Fiction; Pompeii (Extinct city) -- Fiction; Tree houses -- Fiction; Fantasy fiction